Validation of numerically simulated ventricular flow patterns during left ventricular assist device support. Issue 1 (January 2021) - Ghodrati, Mojgan; Khienwad, Thananya; Maurer, Alexander; Moscato, Francesco; Zonta, Francesco; Schima, Heinrich; Aigner, Philipp
Intraventricular flow patterns during left ventricular assist device support have been investigated via computational fluid dynamics by several groups. Based on such simulations, specific parameters for thrombus formation risk analysis have been developed. However, computational fluid dynamic simulations of complex flow configurations require proper validation by experiments. To meet this need, a ventricular model with a well-defined inflow section was analyzed by particle image velocimetry and replicated by transient computational fluid dynamic simulations. To cover the laminar, transitional, and turbulent flow regime, four numerical methods including the laminar, standard k-omega, shear-stress transport, and renormalized group k-epsilon were applied and compared to the particle image velocimetry results in 46 different planes in the whole left ventricle. The simulated flow patterns for all methods, except renormalized group k-epsilon, were comparable to the flow patterns measured using particle image velocimetry (absolute error over whole left ventricle: laminar: 10.5, standard k-omega: 11.3, shear–stress transport: 11.3, and renormalized group k-epsilon: 17.8 mm/s). Intraventricular flow fields were simulated using four numerical methods and validated with experimental particle image velocimetry results. In the given setting and for the chosen boundary conditions, the laminar, standard K-omega, and shear–stress transport methods showed acceptable similarity to experimental particle image velocimetry data, with the laminar model showing the best transient behavior.